ACCIDENTAL POSITIONAL ASPHYXIA IN A CHILD (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Positional asphyxia is a condition arising due to adoption of particular body position that mechanically interferes with pulmonary  ventilation. The phenomenon hardly found any mention in Indian forensic medicine literature. The authors describes here a case  pertaining to 3 years old child, who died due to positional asphyxia in his own house after being entrapped in the space between  the bed and wall of the room. The case also highlights the preventive forensic medicine aspect of such incidents.
Keywords: positional asphyxia; child; Accident